216 High Prevalence of Adenomas and Advanced Adenomas in a Predominantly African-American Population on Free Screening Colonoscopy. (11th January 2018) - Hassan, Muhammad Masood; Khan, Farhan; Naab, Tammey
Abstract: Objectives: Colonoscopy has been shown to reduce colon cancer incidence and risk of death. The risk of progression to carcinoma depends upon the size and number of adenomas with a higher risk in advanced adenomas. Our objective was to evaluate the prevalence of adenomas and advanced adenomas, discovered during free screening colonoscopy, in 52 asymptomatic patients of non-Caucasian ethnicity, predominantly African Americans (AAs). Methods and Materials: This is a retrospective study of 52 patients who underwent free screening colonoscopy in 2016 at an urban hospital serving ethnic minorities. There were 47 AA, three Hispanics, one Asian, and one Caucasian patient enrolled in the study. Twenty-eight were men, and 24 were women. The tissue samples were examined under microscope with standard hematoxylin and eosin stain. The diagnoses of adenoma and advanced adenoma were based on established criteria. Results: Polyps were identified in 51/52 (98%) patients including all women and 27/28 (96%) men. Adenomas were detected in 78.8% cases and advanced adenomas in 35% cases. The adenoma detection rate (ADR) was 92% in men and 81% in women. The advanced adenoma detection rate (AADR) was 27% in men and 42% in women. Conclusion: Our study shows a high prevalence of adenomas and advanced adenomas in AA population when compared to the general population (9.7%-60.5% for men, 3.9%-45.9% for women). Advanced adenoma is defined by the presence of one of the following: high-grade dysplasia, villous component >25%, and/or size >1 cm. The presence of advanced adenoma requires complete excision with clear margins and more frequent surveillance colonoscopy due to a high risk of malignant transformation. Our findings suggest that more frequent colonoscopy may be warranted in AAs. Further studies are required to determine the appropriate age and interval of colonoscopy in AAs.